Pengaruh Work-Life Balance, Lingkungan Kerja, Kepuasan Kerja, dan Stres Kerja Terhadap Produktivitas Karyawan - Gunarti, Indah; Lestari, Setyani Dwi (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of work-life balance, work environment, job satisfaction, and job stress on employee productivity at Bank XYZ. This research uses descriptive quantitative research. The population in this study were all employees of Bank XYZ, with a sample of 172 respondents. Data was collected through questionnaires distributed directly and online. The data analysis method used is multiple linear regression analysis with SPSS 27. The results showed that there is a positive and significant influence between work-life balance on employee productivity. From the results of this analysis, it can be concluded that a good work-life balance contributes positively to increasing employee productivity at XYZ Bank. The work environment has a positive and significant influence on employee productivity. From the results of this analysis, it can be concluded that a good and supportive work environment contributes positively to increasing employee productivity at XYZ Bank. Job satisfaction has a positive and significant effect on employee productivity. From the results of this analysis, it can be concluded that high job satisfaction contributes positively to increasing employee productivity at XYZ Bank. Job stress has no effect on employee productivity. From the results of this analysis, it can be concluded that job stress does not significantly contribute to employee productivity at Bank XYZ.